Gender Wise Comparison of Flipped Classroom Strategy on the Performance of Prospective Teachers - minaz, maksal; Tabassum, Rabia; Ahmad, Ayaz (Advances in Social Sciences Research Journal, 2018)
Flipped classroom make its liberty in the modern technological era to change the passive classroom learning environment in active ones. Flipped classroom is reverse type of classroom learning situation where students do more actively participation. It is a natural phenomenon that every individual of this world has different form one another. Individual differences take place in real classroom situations, and it is also a fact that males and females has different in nature, likes and dislikes, responsibilities and so on. Therefore, present study was aimed to compare the performance of male and female prospective teachers in two different classroom situations. Sample of 48 prospective teachers selected from one of the affiliated college of education in Khyber Pakhtunkhwa (Pakistan) was divided in two equal groups. Where experimental group consist 16 males and 08 female prospective teachers and the control group was consisted 14 females and 10 males. True experimental research design was used and data was collected through pre-test and post-test. The t-test and ANOVA were used for the purpose of data analysis. Data reveled that there was found no gender difference within the groups while the performance of experimental group male and female were outstanding than the performance of control group males and females. The males of experimental group were achieved higher mean scores than the male of control group likewise, female of experimental group were achieved higher scores than the scores of females of control group. Findings of the study are in the favor of flipped classroom strategy therefore, it is recommended that the flipped classroom strategy should be focused by the university teachers as well as policy makers in Pakistan.